The influencing factors of industry innovation networking: evidence from Shanghai's high-tech industry. (17th June 2022) - Cao, Xianzhong; Teng, Tangwei; Zeng, Gang; Bao, Han; Lin, Lan
The influence factor of innovation network is an important research field of human geography. This paper aims to examine the factors, paths, and mechanisms influencing networking of Shanghai's high-tech industry with focus on the biomedical, new material, equipment manufacturing and electronic information. Based on the data from high-tech firms' annual reports by Shanghai's Science and Technology Commission, the results highlight firm development stage, firm scale, and industry position as the main factors promoting innovation networking. In addition, government intervention plays the largest role in the new material industry mainly through investment in innovation activities and taxation intervention in innovation network construction. The impact of firm ownership, spatial location, and intermediary services on the four high-tech industries' innovation networks is relatively smaller. Finally, this study summarises the impact mechanisms for innovation networking in Shanghai's high-tech industries.